THE VIEWS OF THE PARTICIPANTS OF THE EDUCATIONAL PROCESS ON THE STUDENTS' SELF-EVALUATION OF THE RESULTS OF EDUCATIONAL ACTIVITIES - Lidiia Vashchenko (Borys Grinchenko Kyiv Metropolitan University, 2022)
The article examines the significance of the formation of schoolchildren's ability to self-assess the results of educational activities. Self-assessment is an important component of the educational process, which determines the child's personality. According to the results of the survey of research participants, it is shown that teachers support the use of self-assessment of learning outcomes by schoolchildren. If the evaluation system is limited only to checking knowledge and skills in the subject, it does not provide an opportunity to develop critical thinking skills, form motivation for learning, and develop the ability of students to objectively evaluate their results. Regarding the negative results of using the student self-assessment method in the educational process, teachers say that students may have difficulties in self-assessment of their learning results and may not be ready for self-determination and self-recognition of their assessment. Attention was paid to students' understanding of the importance of self-assessment of educational activities. The results of the survey indicate a difference in the views of teachers and students on the formation of the ability to self- assess. Further research can be aimed at developing the internal system of quality assurance in educational institutions, evaluating its effectiveness, using methods of self-assessment of educational and management processes.